Old Drugs, New Indications (Review) - I. I. Miroshnichenko; E. A. Valdman; I. I. Kuz'min (Разработка и регистрация лекарственных средств)
Introduction. The drug can be used in the treatment of one disease and for the prevention and treatment of another pathological process. This is possible due to the repurposing of medicines. Creating drugs from scratch takes a long time to develop and implement, which leads to large financial costs, and also has a high dropout rate of candidate substances and requires significant financial costs. The main advantage of repurposing instead of creating new drug is relatively low financial costs and a significant reduction in the first two phases of clinical trials.Text. Drug repurposing is based on pharmacology, pharmacokinetics, pharmacodynamics, pharmaceuticals and clinical trials, where the first two phases are significantly reduced compared to the creation of a completely new. There are examples of successful repurposing and negative side effects with off-label drug use, which is unsafe but the best solution for orphan diseases. A targeted search for the possibility of repurposing drugs using an automatic procedure is being carried out, where a large number of chemical compounds are tested for activity or affinity for receptors and enzymes – high-throughput screening. Computer design has become widespread, which or repurposing "in silico", where information about the drug is used: targets, chemical structures, metabolic pathways, side effects, followed by the construction of appropriate models. Machine learning (ML) algorithms: Bayes classifier, logistic regression, support vector machine, decision tree, random forest and others are successfully used in biochemical pharmaceutical, toxicological research. But the most promising development of reprofiling is associated with the use of deep neural networks (DNN). Using deep learning, DNN were found to outperform other algorithms for drug development and toxicity prediction.Conclusion. Currently, interest in drug repurposing has grown markedly. A search for the keywords «drug repurposing» showed 2,422 articles on the problem of new uses for drugs that already exist in medicine.